The Effectiveness Of Problem-Based E-Posters On The Learning Outcomes Of Students In Class Vii SMP Muhammadiyah Al-Kautasar Pk Kartasura On Ecological Study - Prabandaru, Aulia; Aryani, Ima (Universitas Islam Negeri Mataram, 2025)
Implementing e-poster media can improve learning outcomes. E-poster media is defined as a poster created using a computer graphics program in a digital format. Problem-Based Learning (PBL) is one learning model based on the constructivist paradigm that focuses on the student's learning process. The integration of e-posters with PBL has the potential to offer challenges that motivate students to actively seek solutions, thereby enhancing their engagement and learning outcomes. This study aims to ascertain the efficacy of problem-based e-poster learning media in influencing student learning outcomes. The research method is descriptive quantitative, employing a pre-test and post-test design with a control or comparison group. The research sample was obtained through purposive sampling, with a total of 120 seventh-grade students from SMP Muhamadiyah Al-Kautsar PK Kartasura participating in the study. The data collection instrument employed a cognitive learning outcome test comprising 20 multiple-choice questions and observation sheets to assess affective and psychomotor domains. The findings indicated that problem-based e-poster media can enhance students' cognitive learning outcomes effectively, with an n-gain value of 0.3791, categorizing it as moderate. Furthermore, the results indicated that 61% of students demonstrated an excellent category in affective learning outcomes, while 67% of students exhibited a good category in psychomotor scores.